Risk of a post-colonoscopy colorectal cancer diagnosis in patients with inflammatory bowel disease: a population-based cohort study - Schønfeldt Troelsen, Frederikke; Sørensen, Henrik Toft; Pedersen, Lars; Erichsen, Rune (Endoscopy, 2021)
Background Post-colonoscopy colorectal cancers (PCCRCs) may account for up to 50 % of all colorectal cancers (CRCs) diagnosed in patients with inflammatory bowel disease (IBD). This may reflect a high colonoscopy frequency; however, evidence remains limited.Methods We conducted a cohort study of IBD and non-IBD patients undergoing colonoscopy. We calculated cumulative incidence proportions (CIPs) of PCCRC at 7–36 months after first-time and subsequent colonoscopies. We also computed crude and adjusted hazard ratios (HRs) of PCCRC, comparing IBD with non-IBD patients undergoing first-time and subsequent colonoscopies. Separate analyses were conducted for consecutive colonoscopies. We calculated 3-year rates of PCCRC to estimate the proportion of IBD and non-IBD CRC patients experiencing PCCRC.Results We observed 138 and 1909 PCCRCs among 34 688 IBD and 358 217 non-IBD patients who underwent colonoscopy. The CIP of PCCRC after first-time colonoscopy was 0.21 % (95 % confidence interval [CI] 0.17 %–0.27 %) for IBD patients and 0.37 % (95 %CI 0.35 %–0.39 %) for non-IBD patients. The adjusted HR of PCCRC after a first-time colonoscopy was 0.96 (95 %CI 0.75–1.22) and the adjusted HRs after subsequent colonoscopies had point estimates around 1.0. The 3-year PCCRC rate was 24.3 % (95 %CI 20.4 %–28.7 %) for IBD and 7.5 % (95 %CI 7.2 %–7.8 %) for non-IBD patients.Conclusions Although PCCRCs accounted for a substantial proportion of all IBD-related CRCs, IBD patients had a low CIP of PCCRC. The elevated 3-year PCCRC rates may, among other factors, stem from the increased colonoscopy frequency in IBD patients.